Analysis Of Work Motivation And Work Stress On Employee Performance With Work Environment As A Variable Intervening At PT Hki Road Construction Pekanbaru-padang Toll Road, Section Siring Field - Satria Wibawa Wahyadyatmika; Kiki Farida Ferine; M. Isa Indrawan (Yayasan Multidimensi Kreatif, 2023)
This study was conducted to test and analyze the effect of work motivation and work stress on employee performance through the work environment as an intervening variable. The location of the research was conducted at PT Hutama Karya Infrastructure for the Construction of the Pekanbaru-Padang Toll Road, Padang Siring Section. The number until this study was 82 respondents who were contract employees. The analysis method used is PLS analysis. The results of the direct influence test showed a positive and significant influence between work motivation on employee performance. There is a positive and significant influence between work motivation and the work environment. There is a positive and significant influence between work stress and employee performance. There is a positive and significant influence between work stress and the work environment. There is a positive but not significant influence between the work environment on employee performance. The results of the indirect influence test showed a positive but not significant influence between work motivation on employee performance through the work environment. There is a positive but not significant influence between work stress on employee performance through the work environment.